2008
DOI: 10.1186/1742-2094-5-45
|View full text |Cite
|
Sign up to set email alerts
|

TNF signaling inhibition in the CNS: implications for normal brain function and neurodegenerative disease

Abstract: The role of tumor necrosis factor (TNF) as an immune mediator has long been appreciated but its function in the brain is still unclear. TNF receptor 1 (TNFR1) is expressed in most cell types, and can be activated by binding of either soluble TNF (solTNF) or transmembrane TNF (tmTNF), with a preference for solTNF; whereas TNFR2 is expressed primarily by microglia and endothelial cells and is preferentially activated by tmTNF. Elevation of solTNF is a hallmark of acute and chronic neuroinflammation as well as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
656
1
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 719 publications
(683 citation statements)
references
References 173 publications
11
656
1
15
Order By: Relevance
“…Astrocytes also produce and release TNF but they are not sensitive to PI3Kd inhibition in vitro as they do not exhibit PI3Kd immunoreactivity, suggesting different trafficking regulators might control TNF release in these cells. The lack of PI3Kd detection in astrocytes in vitro indicates that the observed decrease in astrocytic TNF in vivo under I/R may result from attenuated proinflammatory feedback cascades 5,43,44 stemming from reduced microglial TNF secretion. Our study is in good agreement with other studies pointing to a key role of microglial TNF in early-phase inflammation in the CNS 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes also produce and release TNF but they are not sensitive to PI3Kd inhibition in vitro as they do not exhibit PI3Kd immunoreactivity, suggesting different trafficking regulators might control TNF release in these cells. The lack of PI3Kd detection in astrocytes in vitro indicates that the observed decrease in astrocytic TNF in vivo under I/R may result from attenuated proinflammatory feedback cascades 5,43,44 stemming from reduced microglial TNF secretion. Our study is in good agreement with other studies pointing to a key role of microglial TNF in early-phase inflammation in the CNS 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory models of neurodegeneration propose that systemic inflammation is negatively associated with cognition via increases in neuro-inflammation. Inflammatory cytokines -including Tumor Necrosis Factor(TNF)α, Interleukin(IL)-1β, and IL-6 -secreted by microglia in the brain likely establish and maintain neuro-inflammation (Glass, Saijo, Winner, Marchetto, & Gage, 2010), which can leads to neuronal apoptosis over the long-term (McCoy & Tansey, 2008;Simi, Tsakiri, Wang, & Rothwell, 2007), and inhibits neurogenesis in adults (Ekdahl, Claasen, Bonde, Kokaia, & Lindvall, 2003). Systemic inflammation in the periphery is tied to neuro-inflammation in neurodegenerative disorders (Perry, 2004), as well as in aging populations more generally (Perry, 2010).…”
Section: Inflammation and Cognitive Declinementioning
confidence: 99%
“…[17][18][19][20] TNF also plays an essential beneficial role in a variety of physiological functions including immune surveillance, sleep regulation, synaptic scaling, and neurogenesis. [33][34][35][36][37][38] TNF was initially recognized for its ability to kill tumor cells without harming normal cells. 11 In addition to confirming this antitumor capacity, [12][13][14] early studies also reported that TNF was essential in anti-infection.…”
Section: Discussionmentioning
confidence: 99%